(untitled) (World Economics and Finance Bulletin, 2023)
In our republic, seed production plays an important role in ensuring the abundant harvest of cotton and the high quality of the products obtained from it. This article presents an analysis of the composition, cost and wholesale prices of raw cotton grown in the region by industrial varieties.